STUDIES ON THE PHYTOCHEMICAL SCREENING AND FREE RADICAL SCAVENGING POTENTIALS OF SOLANUM NIGRUM LEAVES EXTRACT - Prasath g, Sriram; ARCHANA PRAKASH,; SRINIVASAN PT,; SUBRAMANIAN S, (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Solanum nigrum is a paramount in medicinal perspective and belongs to family Solanacea. From different parts of the plant significant pharmacological and biological activities have been reported previously. In the present study, the ethanolic extract of leaves was investigated for phytochemical analysis, vitamin and mineral content. Phytochemical analysis of the leaves revealed the presence of phenols, alkaloids, flavonoids, glycosides, saponins, tannins, phytosterols and triterpenoides. The leaves extract was found to contain appreciable amounts of flavonoids and phenols. The extract showed the presence of vitamins such as ascorbic acid, folic acid, and niacinamide. It has been found that the leaves of Solanum nigrum is rich in minerals like copper, magnesium, manganese, vanadium, chromium, calcium, zinc, sodium, and potassium. The antioxidant (free radical scavenging) activity of the extract was determined against 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical, 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) ABTS, Nitric oxide(NO) and Superoxide Scavenging assays. Solanum nigrum leaves extract was found to be antioxidant in nature which is evident from DPPH, ABTS, NO, Superoxide radical scavenging assays. These findings suggest that Solanum nigrum possess biologically important phytoconstituents, significant amounts of vitamins and minerals. IN addition, S. nigrum leaves extract exert free radical scavenging potential in vitro. Key words: Medicinal plants; Solanum nigrum leaves; phytoconstiuents;Antioxidant.